E-074 Emergency Carotid Artery Stenting in Acute Ischemic Stroke. (26th July 2014) - Ohara, N; Tateshima, S; Sayre, J; Duckwiler, G; Jahan, R; Gonzalez, N; Vespa, P; Ali, L; Saver, J; Liebeskind, D
Abstract : Introduction/purpose: Recanalization of occluded arteries is crucial for good functional outcome of acute stroke patients with large vessel occlusion. Endovascular treatment, particularly mechanical thrombectomy, plays an increasing role to achieve rapid recanalization. However, some patients with acute large vessel occlusion have additional extracranial cervical carotid artery occlusion or severe stenosis. Although these patients might undergo carotid stenting to achieve recanalization of intracranial occlusions, such stenting causes challenges in subsequent clinical management. The purpose of this study was to evaluate the safety and efficacy of endovascular recanalization treatment with emergency carotid artery stenting for acute stroke patients. Materials and methods: We analyzed clinical and angiographic data of patients who underwent emergency cervical internal carotid artery (ICA) stenting in the setting of acute endovascular recanalization treatment in our institution between May 2005 and December 2012. Reperfusion was assessed according to the modified Thrombolysis in Cerebral Infarction (mTICI) score. Clinical outcome was evaluated at discharge and at 3 months after treatment by modified Rankin Scale (mRS). Results: 23 patients were included in this cohort. The mean age was 63.3 years. The median NIHSS score on admission was 20 (range, 3–25). The median Alberta Stroke Program Early CT Score on diffusion-weighted imaging (ASPECTS-DWI) on admission was 7 (range, 2–10). 17 patients (73.9%) had ICA occlusion at the origin. 19 patients (82.6%) had intracranial tandem vessel occlusions. All patients successfully underwent carotid artery stenting and 15 patients (65.2%) underwent additional mechanical thrombectomy for intracranial vessels. After the procedure, 9 patients (39.1%) were mTICI grade >IIb. Haemorrhagic transformation with parenchymal hematoma occurred in 9 patients (39.1%) and 2 (8.7%) was symptomatic. At discharge and at 3-months follow-up, 6 patients (26.1%) had a favorable outcome (mRS0–2). The multiple logistic model yielded age (P = 0.018) and initial ASPECTS-DWI (P = 0.029) independently associated with a favorable outcome and additionally mechanical thrombectomy (P = 0.003) was associated with haemorrhagic transformation with parenchymal hematoma. Conclusion: Endovascular recanalization treatment with emergency carotid artery stenting is technically feasible. Further refinement of patient selection may reduce postprocedural hemorrhaghic transformation and optimise resultant clinical outcomes. Disclosures: N. Ohara: None. S. Tateshima: None. J. Sayre: None. G. Duckwiler: None. R. Jahan: None. N. Gonzalez: None. P. Vespa: None. L. Ali: None. J. Saver: None. D. Liebeskind: None.